Failure behavior of undulated sandwich plates under out-of-plane loading - Uzal, Anıl. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
The goal of this thesis study is to understand the failure behavior of an undulated sandwich structure with a particular core design under out-of-plane loading conditions. For this purpose, three-point bending tests are performed. E-glass fiber-reinforced epoxy resin is selected as the material for both core and face sheets. Acoustic emission method is used to detect failure load levels. By carrying out fast Fourier transform technique, failure mechanism originated acoustic waves are investigated in frequency domain in order to identify activated failure modes. The mechanical properties of the composite material required for finite element calculations are obtained by conducting tension tests under real-time acoustic emission monitoring. Besides, theoretical calculations based on micromechanics are performed to determine composite properties and the values provided in the literature are also used. A finite element model of the sandwich structure with obtained mechanical properties is developed to predict the failure behavior and the analytical results are compared with the computational results. By following secant algorithm, critical load level is found. A promising agreement between the finite element model and the experimental results is observed. The successful correlation between the deflection and measured reaction force is obtained. The model succeeds to predict the region of failure accurately.
Keywords: Sandwich construction.